Hubungan Tingkat Kesejahteraan Keluarga dengan Status Gizi di SD Negeri Jejel Kecamatan Ngimbang Lamongan - Yunita Fitasari; Rizal Efendi; Risky Dwi Kartika; Moh. Saifudin; Dadang Kusbiantoro (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The level of family welfare is the key to meeting children's nutritional needs. Parents need to identify nutritional problems experienced by children. Specifically, we want to know how family income affects children's caloric intake. The study used a cross-sectional analytical design. A total of seventy-four youngsters were sampled using the Simple Random Sampling approach. We used a questionnaire to collect data on family welfare levels, measured height and weight to calculate body mass index (BMI), and then ran the numbers through the Chi-Square Test. Among the families surveyed, 43.2% fell into the second group of wealthy, while 51.4% were classified as having normal nutrition. There is a statistically significant correlation between family welfare and children's nutritional status (p = 0.023, r(s) = 0.016, according to the Chi-Square test). The statistics indicate that children's nutritional status is adequate, although there is room for improvement. A child's nutritional condition may be affected by their family's degree of welfare. A child's dietary requirements are better met in families with greater levels of welfare. For optimal growth and development, it is expected that parents would attend to their children's dietary requirements